ANALISIS PROJEK PENGUATAN PROFIL PELAJAR PANCASILA PADA TEMA KEWIRAUSAHAAN - Rizky Aulia Rahmani; Choirul Huda; Siti Patonah; Paryuni Paryuni (Universitas Negeri Medan, 2023)
Abstract: This study aims to describe the implementation of a project to strengthen Pancasila student profiles on the theme of entrepreneurship at SDN Gajahmungkur 04. This research uses a qualitative approach with descriptive methods. Sources of data from this study were school principals, class teachers and grade IV students, totaling 28 people. The collection technique is interviews, and uses observations that are directly involved with P5 activities on the observed objects. The results of the study show that the application of the independent curriculum can encourage an entrepreneurial spirit through P5 with the theme of Entrepreneurship. This results in increased innovation, motivation to contribute actively and creatively to present students' ideas through actions that can have a good impact on students. Keyword: Pancasila Student Profile Strengthening Project, Entrepreneurship, Freedom Curriculum Abstrak: Penelitian ini bertujuan untuk mendiskripsikan pelaksanaan projek penguatan profil pelajar pancasila tema kewirusahaan di SDN Gajahmungkur 04. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Sumber data dari penelitian ini adalah kepala sekolah, guru kelas dan siswa kelas IV yang berjumlah 28 orang. Teknik pengumpulannya adalah wawancara, dan menggunakan observasi yang terlibat langsung dengan kegiatan P5 pada objek yang diamati. Hasil penelitian menunjukkan bahwa pengaplikasian kurikulum merdeka dapat mendorong jiwa kewirusahaan melalui P5 dengan tema Kewirausahaan. Hal ini mengakibatkan peningkatan inovasi, motivasi untuk berkontribusi aktif dan kreatif untuk menghadirkan ide-ide siswa melalui tindakan yang bisa memberikan dampak baik bagi siswa.Kata Kunci: Projek Penguatan Profil Pelajar Pancasila, Kewirausahaan, Kurikulum Merdeka